In Situ Polymerization of Nylon 66/Reduced Graphene Oxide Nanocomposites. (13th September 2018) - Duan, Xiaochao; Yu, Bin; Yang, Tonghui; Wu, Yanpeng; Yu, Hao; Huang, Tao
Abstract : A one-step method of in situ polymerization of nylon 66/reduced graphene oxide (PA66/rGO) nanocomposites is first proposed, simply by introducing graphene oxide (GO) into PA66 salt with the existence of ammonium hydroxide. The GO is prereduced by the ammonium hydroxide at an early stage of the polymerization process and then grafted on the PA66 chains, accompanied with the thermal reduction of GO. The PA66 chains were grafted onto the GO nanosheets through the condensation between the oxygen-containing functional groups of the GO and the terminal amino ends of the PA66 chains. The effect of GO on the mechanical properties, especially tensile strength, of nanocomposites was investigated. The results revealed that the incorporation of a very small amount (about 1 wt%) of GO caused a significant improvement in ultimate tensile strength (about 17%). The SEM of the fracture surface of composites indicated a good dispersion of rGO in the matrix. Raman spectroscopy, thermogravimetric analysis (TGA), scanning electron microscope (SEM), Fourier transformed infrared spectroscopy (FTIR), and XRD patterns of rGO, which was isolated from nanocomposites, revealed that the GO nanolayers were simultaneously reduced and PA66 chains were grafted on the rGO nanosheet during the polymerization process. The rGO grafted with the PA66 chain increases its compatibility in the PA66 matrix and effectively enhanced the interfacial energy of the composites.